Lietuviška knyga Pirmojo pasaulinio karo metais - Stonienė, Vanda (Knygotyra, 1992)
The development of Lithuanian book publishing was severely hampered during World War I. In 1915, Lithuania was occupied by German military forces, and no activities of cultural institutions were allowed without permission from the occupiers. A single newspaper, Dabartis, was published from 1915 onwards by them. Additionally, the Catholic society was later permitted to have its periodical edition, Ateitis. Only at the beginning of 1918, under the threat of the complete failure of their colonial plans, did the occupiers allow the publishing of Lithuanian newspapers such as Lietuvos aidas, Tėvynės sargas, and Darbo balsas. The military occupation regime, everyday life difficulties, and harsh censorship exerted an extremely negative influence on the publishing of Lithuanian books. Every edition required official permission from the German military authorities. Therefore, only textbooks, annual almanacs, and small popular science editions could mostly be issued. Publication work was carried out by the Lithuanian Scientific Society, St. Casimir’s Society, and the M. Slapėnienė bookshop. The demand for books among the population of Lithuania was high, but it was impossible to satisfy it. Additionally, the occupiers closed almost all large libraries, and even the transport of books was completely banned. In 1915, under the conditions of the approaching front line, about 300,000 inhabitants and many institutions were forced to withdraw from Lithuania. In St. Petersburg, Moscow, Voronezh, and other Russian cities, large colonies of Lithuanian refugees were formed. They were mostly supported by the Lithuanian Society of War Refugees. This society, established in St. Petersburg, published its newspaper Lietuvių balsas, founded some schools for Lithuanian pupils, organized training courses for adults, and issued several textbooks and other books. During the war period, the society published about 50 Lithuanian editions. Other charitable societies also organized some editions. In 1918, Lithuanian refugees began returning to their homeland. The Lithuanian Society of War Refugees continued its activities until February 1918, when its cultural work was banned by the Soviet power.